2005
DOI: 10.2307/3473152
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Mutual Sexual Selection on Homologous Signal Traits in Drosophila serrata

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The evolution of female mating preferences has received considerable attention in sexual selection theory (Andersson 1994), but the importance of male mating preferences and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
210
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(225 citation statements)
references
References 29 publications
14
210
1
Order By: Relevance
“…2014). To test the overall contribution of linear and nonlinear effects in our models, we used partial F ‐tests (Chenoweth and Blows 2005). We also calculated phenotypic correlations between male traits.…”
Section: Methodsmentioning
confidence: 99%
“…2014). To test the overall contribution of linear and nonlinear effects in our models, we used partial F ‐tests (Chenoweth and Blows 2005). We also calculated phenotypic correlations between male traits.…”
Section: Methodsmentioning
confidence: 99%
“…Although the phenotypic con-sequences of female preference are well described (Jennions and Petrie 1997), much less is known about the genetic basis of female preferences and, subsequently, how female preferences evolve. A number of studies have demonstrated that female preference is heritable (Bakker and Pomiankowski 1995;Jennions and Petrie 1997;Chenoweth and Blows 2006), but the inherent difficulties in quantifying mating preferences (Wagner 1998;Chenoweth and Blows 2006) have limited the application and scope of quantitative genetic experiments on such traits.…”
mentioning
confidence: 99%
“…First, by determining which males in a population do and which do not gain mates, a population-level preference can be determined. This type of measure of female preferences is particularly useful in estimating the strength of sexual selection operating on male display traits (Kingsolver et al 2001a;Chenoweth and Blows 2006). However, such measures are not informative about variation among females in their preferences for male traits (Wagner 1998) and are therefore not amenable to genetic analyses.…”
mentioning
confidence: 99%
See 2 more Smart Citations